PERAN GURU DALAM MENGEMBANGKAN INTERAKSI SOSIAL ANAK AUTISME DI SKH ELMYRA SHANUM - Siti Sarah; Yahdinil Firda Nadhirah (STKIP Subang, 2024)
about the role of class teachers and special assistant teachers in dealing with students with autism disorders in elementary schools. And to describe the characteristics of children with autism and how the active role of parents and teachers in improving the communication and social interaction skills of children with autism, children to adapt to the disorder and effective development interventions and improve the quality of life of children with autism and parents who care for them. The research method used is descriptive qualitative which describes and explains the role of teachers in developing children with autism at SKH Elmyra Shanum in Serang. Data collection methods use observation techniques, interviews, documentary research. Data collection tools in the form of audio recordings at SKH Elmyra Shanum. This study shows that there is a significant relationship between the active role of parents and school teachers in improving children's communication and social interaction skills. The most important thing given to children is parental acceptance of children and social support provided by parents and teachers in the child's environment